Circ_0078767 suppresses non‐small‐cell lung cancer by protecting RASSF1A expression via sponging miR‐330‐3p. (3rd December 2018) - Chen, Ting; Yang, Zuozhang; Liu, Chao; Wang, Li; Yang, Jun; Chen, Long; Li, Wenhui
Abstract : Objectives: This study was designed to investigate the role of circ_0078767/miR‐330‐3p/RASSF1A in non‐small‐cell lung cancer (NSCLC). Bioinformatic analysis was performed to screen for the differentially expressed genes in NSCLC tissues from adjacent lung tissues. Materials and Methods: qRT‐PCR was used to detect the RNA expression of genes in cells and tissues, and Western blot was conducted to determine the protein levels of RASSF1A in tissues and cells. A miRanda algorithm was used to predict the targeted relationship among RNAs. A dual‐luciferase reporter gene assay was conducted to verify the targeted relationship. Flow cytometry was performed to investigate the effects of circ_0078767/miR‐330‐3p/RASSF1A on cell cycle progression and apoptosis. A CCK‐8 assay was conducted to explore the effects of circ_0078767/miR‐330‐3p/RASSF1A on cell proliferation. A transwell invasion assay was completed to study the effects of circ_0078767/miR‐330‐3p/RASSF1A on cell invasion. Lastly, an in vivo assay was conducted to investigate the effects of circ_0078767/miR‐330‐3p/RASSF1A on tumour development. Results: Circ_0078767 and RASSF1A were downregulated, while miR‐330‐3p was upregulated in NSCLC tissues than that in adjacent tissues. miR‐330‐3p had a binding relationship with circ_0078767 and RASSF1A. The overexpression of circ_0078767 and RASSF1A or the underexpression of miR‐330‐3p significantly suppressed NSCLC cell viability, cell cycle progression and invasion while also significantly promoting cell apoptosis. Additionally, these modulations significantly suppressed in vivo tumour growth. Conclusions: Circ_0078767 could suppress NSCLC progression by inhibiting miR‐330‐3p, which thereby increased RASSF1 levels.